Water Quality of Perturbed Egbokodo River, Delta State, Nigeria - Isibor, Dr. Patrick Omoregie; Izegaegbe, Joshua Idowu; Feeman, Oluowo Elohor (International Journal of Environmental Sciences, 2016)
Purpose: An aquatic ecological survey was carried out across the stretch of Egbokodo River; located in Warri South Local Government Area of Delta State, Nigeria. Biomonitoring survey of the river was carried out around important sections along the river. Methodology: 10 samples of surface water were collected at 10 sub-stations; marked using the Global Positioning System device (GPS); randomly around each station (1, 2, 3, 4, and 5) from November, 2014 to February, 2016 (16 months). The pH of water was taken and recorded in-situ using a WTW water sampler probe. All samples were transported immediately to the laboratory for analysis of the physico-chemical variables. The mean and standard error values of 10 samples collected from each station were subjected to a two-way analysis of variance (ANOVA) to analyse the differences across the stations and the months; using SPSS version 19.2 at probability level of 0.05. Duncan Multiple Range test (DMR) to ascertain the actual locations of the significant differences across the stations and among the months. Results: Results show that anthropogenic activities around the river are of higher impacts on the ecological equilibrium than most neighbouring rivers. Data assures the suitability of the river for aquatic life, agriculture and domestic use. However, need for amelioration of the anthropogenic perturbations cannot be overemphasised. High conductivity in the dry season was coeval with high salinity; indicating a substantial contribution of the dissolved salts to the conductivity of the river. The high values of BOD observed at Station 2 was accompanied by low dissolved oxygen (DO). This can be attributed to disposal of organic wastes at this section of the river. The DO at Station 3 was significantly higher than other stations throughout the study period (P < 0.05). This can be attributed to the surface turbulence by dredging agitation and high standing aquatic macrophytes. The levels of the essential primary productivity nutrients such as nitrate, phosphate and sulphate in the river indicate that the river is oligotrophic. Conclusion and Recommendations: The study has provided a proof of trophic stratification by anthropogenic perturbations. The study has also provided a general picture of the aquatic environment over an extended period of time; a database useful for reference in subsequent studies aimed at protecting the ecological integrity Egbokodo River.